The young gymnast - Zetaruk, M. N. (Clinics in Sports Medicine, 2000)
Gymnastics training develops strength, flexibility, concentration, balance, grace, and speed in young athletes. In terms of hours per week and intensity of practice, the dedication to training at a young age, is unparalleled in most other youth sports. With this dedication comes the risk of injury to the immature musculoskeletal system, and it is our duty to ensure that these risks are minimized. Through adequate safety equipment, supervision, and spotting of difficult techniques, a number of acute injuries may be prevented. Maintenance of balanced flexibility and strength, modification of training to limit pain, and taping or splinting of wrists and ankles may reduce the risk of overuse injuries. Physician who deal with young gymnasts must have an understanding of the inherent risks of the sport to provide prompt diagnoses and appropriate management of injuries. The gymnasium can be a healthy environment as long as the health and safety of the child takes precedence over the success of the gymnast.